The Readiness of the National Health System in Facing a Global Health Crisis - Seno Lamsir (PT. Anagata Sembagi Education, 2025)
National health system preparedness is a critical determinant of a country’s ability to respond to increasingly frequent global health crises. This study analyzes Indonesia’s readiness through a Systematic Literature Review (SLR) using PRISMA 2020 guidelines. A total of 67 articles from 742 identified publications were reviewed to assess technical capacity, governance, financing, workforce readiness, and digital health integration. Findings indicate that Indonesia has made progress in laboratory expansion, digital health initiatives, and intersectoral coordination. However, structural challenges remain, including unequal distribution of health facilities, limited workforce density, fragmented information systems, and insufficient health financing. The study highlights that preparedness must be multidimensional by strengthening real-time surveillance, integrated digital systems, sustainable financing, and responsive cross-sector governance. The results provide evidence-based insights to support long-term strategies for building a more resilient national health system capable of confronting future global crises